2018
DOI: 10.1038/s41598-018-27288-2
|View full text |Cite
|
Sign up to set email alerts
|

Sensory dominance and multisensory integration as screening tools in aging

Abstract: Multisensory information typically confers neural and behavioural advantages over unisensory information. We used a simple audio-visual detection task to compare healthy young (HY), healthy older (HO) and mild-cognitive impairment (MCI) individuals. Neuropsychological tests assessed individuals’ learning and memory impairments. First, we provide much-needed clarification regarding the presence of enhanced multisensory benefits in both healthily and abnormally aging individuals. The pattern of sensory dominance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 60 publications
2
40
0
1
Order By: Relevance
“…Finally, we tested for topographic differences using global dissimilarity and a non-parametric permutation test. In all analyses, effects were considered reliable if significant differences were observed for a minimum of 20 ms contiguously (Guthrie and Buchwald 1991 ; Murray et al 2018 ). For full-term infants there was no evidence of neural response differences between paired multisensory and summed unisensory conditions in either global field power or global dissimilarity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we tested for topographic differences using global dissimilarity and a non-parametric permutation test. In all analyses, effects were considered reliable if significant differences were observed for a minimum of 20 ms contiguously (Guthrie and Buchwald 1991 ; Murray et al 2018 ). For full-term infants there was no evidence of neural response differences between paired multisensory and summed unisensory conditions in either global field power or global dissimilarity.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found impairments among five senses (operationalized as global sensory impairment) predicted lower cognitive function but did not test for graded effects (17). Assessment of multiple types of sensory function may be a valuable tool for identifying older adults at high risk of poor health outcomes including cognitive decline (35). Future research should examine whether diagnostic and prognostic predictions for patients are improved by including multisensory assessments and whether interventions to prevent dementia could be targeted to those with multisensory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The MCI group's persistent postural destabilization after visual stimulation cessation may have been caused by their loss of ability to quickly downweigh the importance of visual information during postural stabilisation. This top-down inhibition of sensory information may be mediated by the cholinergic system, which is deficient in patients with subcortical vascular lesions associated with MCI (Murray et al, 2018;Liu et al, 2017). We also observed similar difficulties with downweighing visual information and fusing different sensory modalities when adaptation was needed in subjects with Parkinson's disease (PD), which is associated with subcortical cognitive impairment (Hwang et al, 2016).…”
Section: Notesmentioning
confidence: 71%